2023
DOI: 10.3390/ijerph20053819
|View full text |Cite
|
Sign up to set email alerts
|

Motor Development Comparison between Preterm and Full-Term Infants Using Alberta Infant Motor Scale

Abstract: The Alberta Infant Motor Scale (AIMS) was developed to evaluate the motor development of infants up to 18 months of age. We studied 252 infants in three groups (105 healthy preterm infants (HPI), 50 preterm infants with brain injury (PIBI), and 97 healthy full-term infants (HFI) under 18 months, corrected age (CoA)) using AIMS. No significant differences were found among HPI, PIBI, and HFI in infants less than 3 months old, yet significant differences were noted in positional scores (p < 0.05) and total sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…However, even if an age correction were to be implemented, there is a specific delay in motor development in 41% of cases, among the analyzed subjects. Also, Ko J. et al [ 21 ], analyzing motor development between preterm and full-term infants, in a study of 252 subjects between 4 and 9 months of age, identified significant differences in motor development. The motor landmarks evaluated were in four distinct positions (ventral recumbency, supine recumbency, sitting, and standing positions).…”
Section: Discussionmentioning
confidence: 99%
“…However, even if an age correction were to be implemented, there is a specific delay in motor development in 41% of cases, among the analyzed subjects. Also, Ko J. et al [ 21 ], analyzing motor development between preterm and full-term infants, in a study of 252 subjects between 4 and 9 months of age, identified significant differences in motor development. The motor landmarks evaluated were in four distinct positions (ventral recumbency, supine recumbency, sitting, and standing positions).…”
Section: Discussionmentioning
confidence: 99%